A Nursing Approach to Improving Critical Care Compliance With Vital Signs and Neurological Assessments in Post-IV-Alteplase Stroke Patients. Issue 4 (October 2022) - Cohen, Vicki L.; Anderson, Amanda; Noah, Patty; Super, Jamie
Abstract : Ischemic stroke represents 87% of all strokes. As global initiatives move forward with stroke care, health care providers and institutions will be called on to deliver the most current evidence-based care. The American Heart Association/American Stroke Association (AHA/ASA) estimates that 795 000 strokes occur each year; 610 000 are new strokes, and 185 000 are recurrent strokes. Eighty-seven percent are ischemic strokes; the overall mortality rate from stroke was 273 000, which makes stroke the fifth leading cause of death and the leading cause of disability in the United States. Stroke costs the United States an estimated $34 billion each year. This article outlines a nursing intervention regarding the use of intravenous thrombolytic therapy for treating acute ischemic stroke, the risk factors related to IV-alteplase, best-practice protocols, and the nursing role in efforts to deliver safe care. The conclusion reveals the need for health care organizations to explore opportunities, continually inspire innovation at the bedside, highlight nursing's essential contribution to acute stroke care, and encourage publishing improvements in patient care and the nurse practice environment.